Locating passive tags using radio frequency identification technology in an enclosed area - Wong, Jie Hong. (2010)
The focus of this project is to review the various methods of implementing the Radio Frequency Identification (RFID) Technology to locate items within an enclose space. This provides a cheaper alternative as compared to Global Positioning System(GPS) or infrared, and utilizing passive tags will enable the system to be installed with ease and affordability. Such implementation has been researched by others, however, most research were done by using the active tag system. Such system can have further communication range; however, they are limited by their battery capacity and are very dependent on it. Therefore, to implement this localization system using passive tag would eliminate the dependency on the battery and lower the cost of implementation. With the short-term loan of each antenna, I was able to carry out only a particular test using each of the antennas. I have used SAMSys for the Read Count Method and Astra for the RSSI Method. The collected data, or the profiling, of each antenna can be used for future research or implementation. The data logging was done in an ideal indoor environment, with no objects or obstructions around. In summary, from the data collected and the research done, it is seen feasible to implement the localization system with Passive tags. As the performance is about the same as an active system, the implementation cost will be greatly reduced.